PENGARUH ORIENTASI ETIKA, RASIONALISASI DAN SELF EFFICACY TERHADAP KECURANGAN AKADEMIK - rika adriyana (Jurnal Ekonomi Dan Bisnis, 2019)
ABSTRACTThis study aimed to examine the effect of Ethical Orientation of Idealism and Relativism, Rationalization, and Self efficacy on Academic Fraud. Sampling is accidental sample selection method used. The sample were accounting students at The Economic Faculty, Universitas Pekalongan were 240 students who. Data collecting method by questionnaire. Quantitative analysis method consisting of validity test, reliability test, autocorrelation test, classical assumption test, and statistical test of t. Hypothesis testing using multiple regression by using SPSS Version 2.1. Research finding showed that idealism have a negatif and significant effect on academic fraud. While  relativism  have a negatif and significant effect on academic fraud. And then razionalization and self efficacy positifly and significantly effect on academic fraud. Keywords : idealism, relativism, rasionalization, self efficacy and academic fraud.